Single Pole Double Throw Discrete PIN Diode Switch with Switchable Quater Wave Stub Resonator - Shairi, Noor Azwan; Ahmad, Badrul Hisham; Zakaria, Zahriladha; Peng Wen, Wong (2012)
Generally, it is difficult to get very high isolation of Single Pole Double Throw (SPDT) switch at 2.3 to 2.7 GHz band using single low performance discrete PIN diode (suitable up to 3 GHz applications). Therefore, this paper proposed switchable quarter wave stub resonator for isolation improvement of SPDT discrete PIN diode switch for Time Division Duplex switching of WiMAX and LTE front-end system at 2.3 to 2.7 GHz band. The commercialized discrete PIN diodes are used to switch between short stub and open stub where the Q of the resonator has been studied and analyzed for application of SPDT switch design. In measurement result, the SPDT switch with switchable quarter wave stub resonator has shown more than 30 dB of Tx-Rx isolation at 2.3 to 2.7 GHz band giving better isolation compared to conventional series SPDT switch.